A Security Model for an Operating System for Security-Critical Applications in Small Office and Home Environment - Janacek, Jaroslav (Communications - Scientific letters of the University of Zilina, 2009)
Personal computers are often used in small office and home environment for different purposes ranging from general web browsing and e mail processing to processing data that are sensitive regarding their confidentiality and/or integrity. Common operating systems do not provide sufficient protection. We present asecurity model combining the well known benefits of mandatory access control in classified information processing systems with the typical home and small office computer use. We use a simple two-dimensional data classification scheme and present a security model with provable properties that significantly reduces the risks of confidentiality and/or integrity protection violation.